Treinamento de força realizado até a falha muscular versus não falha: efeitos na massa, força, ativação e arquitetura muscular de homens jovens treinados - Silva, Natalia Santanielo (Universidade Federal de São Carlos, 2019)
The aim of the study was to compare the effect of resistance training (RT) performed to muscle failure (RT-F) or non-failure muscular (RT-NF) on muscle mass, muscle architecture and activation in trained young men. Thigh lean mass (TLM), vastus lateralis muscle cross-sectional area (CSA), architecture and 1-RM test were assessed at baseline (pre) and after ten (post) RT weeks. EMG amplitude assessment was performed after 10W RT. 14 young trained men participated in the present study were (23 ± 2.3 years, 171.7 ± 5.0 cm, 73.9 ± 5.8 kg). All protocols were similarly effective in increasing TLM (RT-F: 6371.7 ± 629.7 g to 6867.7 ± 657.8 g, RT-NF: 6401.1 ± 587.8 g to 6798.4 ± 610.0 g; P < 0.0001) and CSA (RT-F: 32.9 ± 5.3 cm2 to 37.7 ± 5.6 cm2, RT-NF: 33.1 ± 5.8 cm2 to 37.5 ± 6.6 cm2; P < 0.0001) from pre- to post-training. Both protocols showed significant increases in 1-RM values from pre- to post-training for 45° leg press (RT-F: 237.5 ± 21.6 kg to 290.0 ± 40.2 kg, RT-NF: 237.5 ± 32.9 kg to 299.9 ± 41.4 kg; P < 0.0001), leg extension (RT-F: 55.6 ± 8.6 kg to 73.2 ± 9.8 kg, RT-NF: 56.3 ± 9.5 kg to 73.8 ± 8.4 kg; P < 0.0001), and leg flexion (RT-F: 53.5 ± 8.0 kg to 64.3 ± 6.4 kg, RT-NF: 51.57 ± 7.9 kg to 63.2 ± 6.8 kg; P < 0.0001). EMG amplitude showed no significant differences between protocols (P > 0.05). In relation to the muscular architecture, both the pennation angle (PA) (TF-F: 22.5 ± 3.8º for 25.5 ± 3.8º, TF-NF: 23.1 ± 2.5º for 26.0 ± (P <0.0001) and the muscle fasciculus length (FL) (TF-F: 5.5 ± 0.53 cm for 6.0 ± 0.5 cm; TF-NF: 5.5 ± 0,5 cm for 6.0 ± 0.6 cm, P < 0.0001) showed significant increases from pre to pos-training. In conclusion, RT-F or RT-NF are equally efficient in promoting increases in muscle hypertrophy, and muscle strength, EMG amplitude, and muscle architecture.
Resistance training performed until muscle failure versus no failure: effects mass, strength, activation and architecture muscle of trained young men
Keywords: Falha concêntrica; Adaptações neuromusculares; Área de secção transversa; Eletromiografia; Fadiga; Concentric failure; Neuromuscular adaptations; Muscle cross-sectional area; Electromyography; Fatigue.; CIENCIAS BIOLOGICAS::FISIOLOGIA